Developing an English for Nutritionists Textbook: A Research and Development Study of Nutrition Department in Bengkulu Health Polytechnic - Ade Sissca Villia (UNIB Press, 2026)
This study aims to develop an English for Nutritionists textbook, specifically designed to address the unique linguistic and professional needs of nutrition students in Indonesia. Despite the availability of English for Specific Purposes (ESP) textbooks in health sciences, existing resources often fail to meet the specific needs of nutrition students, as they focus predominantly on general medical English. A comprehensive needs analysis was conducted, involving interviews with lecturers and an evaluation of current ESP resources. Based on the findings, a prototype textbook was developed that incorporates nutrition-specific content such as food labeling, dietary guidelines, and case studies, along with task-based activities to enhance reading, writing, speaking, and listening skills. The development followed a systematic Research and Development (R&D) approach, including needs assessment, prototype development, and validation by experts. The textbook's content, presentation, and language were found to be highly relevant and valid for the target audience, with an expert validation mean score reflected in an Aiken’s V index of 0.839, indicating a high level of content validity. The results indicate that the developed textbook effectively addresses the gap in available resources by integrating both linguistic and professional knowledge. This study concludes that a specialized ESP textbook for nutrition students can significantly enhance their English proficiency and professional preparedness, supporting their academic and career development in the global nutrition field.